Spotlight on unmet needs in stroke prevention: The PIONEER AF-PCI, NAVIGATE ESUS and GALILEO trials - Hemmrich, Melanie; Peterson, Eric D.; Thomitzek, Karen; Weitz, Jeffrey I. (Thrombosis and Haemostasis, 2016)
Atrial fibrillation (AF) is a major healthcare concern, being associated with an estimated five-fold risk of ischaemic stroke. In patients with AF, anticoagulants reduce stroke risk to a greater extent than acetylsalicylic acid (ASA) or dual antiplatelet therapy (DAPT) with ASA plus clopidogrel. Non-vitamin K antagonist oral anticoagulants (NOACs) are now a widely-accepted therapeutic option for stroke prevention in non-valvular AF (NVAF). There are particular patient types with NVAF for whom treatment challenges remain, owing to sparse clinical data, their high-risk nature or a need to harmonise anticoagulant and antiplatelet regimens if co-administered. This article focuses on three randomised controlled trials (RCTs) that are investigating the utility of rivaroxaban, a direct, oral, factor Xa inhibitor, in additional areas of stroke prevention where data for anticoagulants are lacking: oPenlabel, randomized, controlled, multicentre study explorIng twO treatmeNt stratEgiEs of Rivaroxaban and a dose-adjusted oral vitamin K antagonist treatment (PIONEER AF-PCI); New Approach riVaroxoban Inhibition of factor Xa in a Global trial vs Aspirin to prevenT Embolism in Embolic Stroke of Undetermined Source (NAVIGATE ESUS); and Global study comparing a rivAroxaban-based antithrombotic strategy to an antipLatelet-based strategy after transcatheter aortIc vaLve rEplacement to Optimize clinical outcomes (GALILEO). Data from these studies present collaborative efforts to build upon existing registrational Phase III data for rivaroxaban, driving the need for effective and safe treatment of a wider range of patients for stroke prevention.
Keywords: Stroke prevention; atrial fibrillation; percutaneous coronary intervention; transcatheter aortic valve replacement; rivaroxaban